2022
DOI: 10.1098/rsos.212025
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cu(OH) 2 nanowires modified by Fe 3 O 4 @SiO 2 nanocomposite via green and innovative method with antibacterial activity and investigation of magnetic behaviours

Abstract: In this study, green synthesis of modified Cu(OH) 2 nanowires by Fe 3 O 4 @SiO 2 core–shell nanospheres was easily performed via chemical reduction. In other words, the direct coating of Cu(OH) 2 on Fe 3 O 4 @SiO 2 was successfully realized without the extra complicated procedures. Various concentrations of synthesized na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…This is shown in (Fig. 1 ) 49 . According to the weight percentage table of the components of the Fe 3 O 4 /Se nanocomposite, the most abundant element in this nanocomposite was Fe, which had the highest weight percentage (37.25%), followed by oxygen (32.93%), which had the highest weight ratio, and selenium (29.82), which had the appropriate weight percentage.…”
Section: Resultsmentioning
confidence: 59%
“…This is shown in (Fig. 1 ) 49 . According to the weight percentage table of the components of the Fe 3 O 4 /Se nanocomposite, the most abundant element in this nanocomposite was Fe, which had the highest weight percentage (37.25%), followed by oxygen (32.93%), which had the highest weight ratio, and selenium (29.82), which had the appropriate weight percentage.…”
Section: Resultsmentioning
confidence: 59%
“…Moreover, Cu has been found to interfere with biofilm formation, which plays a crucial role in bacterial resistance. Cu ions disrupt the extracellular matrix of biofilms, preventing their formation and rendering them more susceptible to antimicrobial agents 80 . In our study, we observed that incorporation Cu into Ti surfaces enhanced their antibacterial properties compared to Ti alone.…”
Section: Resultsmentioning
confidence: 99%